Description of the covid-19 pandemic on community income in Tomuan Dolok village, Simalungun district - Nurmala Dewi Ria Lestari; Jumadiah Wardati; Tresia Melianna Simanjuntak; Novitas Sinaga (Institute of Computer Science (IOCS), 2022)
Corona virus or severe acute respiratory syndrome coronavirus 2 (SARSCOV-2) is a virus that attacks system breathing . Disease Because infection with this virus called COVID-19. Objective study This is For know description the covid-19 pandemic against income community in Tomuan Dolok . Design used _ in study This done with descriptive with cross sectional approach , where study This done only on One period certain And taking sample done in very time course , no There is repetition in data collection . From the results of the preliminary survey on residents of Tomuan mountain with give questionnaire about income before And after happening the covid-19 pandemic got that before the occurrence of covid-19 income resident the Still stable , meanwhile after the occurrence of covid-19 income resident the decreased . Results research conducted in the village Tomuan Mountain regency Simalungun , obtained results namely : From the group income res»onden , respondents whose income lower namely 20 people (79.1%) more Lots than class income medium And income top . From respondents argue more covid-19 pandemic many argue _ not enough namely 18 people (79.1 % ) than argue Enough And argue ok . From the results tabulation afternoon between class income respondent And opinion the covid-19 pandemic . that is respondent class income lower more Lots namely 18 people (79.1%) with score less <60. From the results study on expected society still guard health And obey rule during period the covid-19 pandemic .